2019
DOI: 10.1021/acs.jafc.9b03432
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Wheat Thaumatin-like Protein That Inhibits Saccharomyces cerevisiae

Abstract: Plants often produce antifungal peptides and proteins in response to infection. Also wheat, which is the main ingredient of bread dough, contains such components. Here, we show that while some industrial strains of the baker's yeast Saccharomyces cerevisiae can efficiently ferment dough, some other strains show much lower fermentation capacities because they are sensitive to a specific wheat protein. We purified and identified what turned out to be a thaumatin-like protein through a combination of activity-gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Since a sufficient CO 2 production during fermentation is important to obtain an optimal loaf volume, the CO 2 production profiles of the selected strains in Terroir whole wheat dough were determined by using a Risograph device. Van der Maelen and co-workers showed a reduced fermentation capacity of one in six S. cerevisiae strains (Van Der Maelen et al, 2019). However, as shown in Figure 4A, the selected strains were able to ferment in the whole wheat dough, but the CO2 production rate in dough varied according to the yeast strain used.…”
Section: Co 2 Production Profiles Of the Selected Yeast Strains In Whmentioning
confidence: 95%
“…Since a sufficient CO 2 production during fermentation is important to obtain an optimal loaf volume, the CO 2 production profiles of the selected strains in Terroir whole wheat dough were determined by using a Risograph device. Van der Maelen and co-workers showed a reduced fermentation capacity of one in six S. cerevisiae strains (Van Der Maelen et al, 2019). However, as shown in Figure 4A, the selected strains were able to ferment in the whole wheat dough, but the CO2 production rate in dough varied according to the yeast strain used.…”
Section: Co 2 Production Profiles Of the Selected Yeast Strains In Whmentioning
confidence: 95%
“…Most of the TLP proteins reported have antifungal activity under in vitro conditions, so they have potential application value in the biological control of plant pathogens. A previous report showed that recombinant TLP from wheat was confirmed to have inhibitory activity against Saccharomyces cerevisiae [26]. A Panax notoginseng recombinant PnTLP2 expressed in Escherichia coli has antifungal effects in Alternaria panax and Alternaria alternata [11].…”
Section: Introductionmentioning
confidence: 98%